2006
DOI: 10.1071/ea05117
|View full text |Cite
|
Sign up to set email alerts
|

Effect of silicon on the morphology of shoots and roots of alfalfa (Medicago sativa)

Abstract: A silicon (Si)-deficient top soil was used in a pot experiment to investigate the effect of Si application on the shoot and root morphology of alfalfa (Medicago sativa L.). Silicon was applied to the alfalfa plants at 6 different rates (0, 0.025, 0.05, 0.10, 0.20, 0.30 g/kg), and each treatment was replicated 6 times. This study indicated that the Si content of roots and shoots increased significantly (P<0.05) with increasing Si concentration in the soil, and that the Si content of roots was greater than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 23 publications
3
16
0
Order By: Relevance
“…The longest shoots were observed when Actisil in concentration of 0.3% and 0.4% was applied in the tunnel. The obtained results confirm the research of other authors who noted that an application of silicate increased height of plants of Medicago sativa, Calendula officinalis, Rosa 'Kardinal' Gerbera hybrida 'Acapella' and many other [Walter 2004, Guo et al 2006, Kamenidou et al 2010, Bayat et al 2013, Whitted-Haag et al 2014, Dębicz et al 2016. A reaction of plants and varieties to silicon application might be related to different levels of endogenous gibberellins, what is suggested by Sivanesan et al [2013].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The longest shoots were observed when Actisil in concentration of 0.3% and 0.4% was applied in the tunnel. The obtained results confirm the research of other authors who noted that an application of silicate increased height of plants of Medicago sativa, Calendula officinalis, Rosa 'Kardinal' Gerbera hybrida 'Acapella' and many other [Walter 2004, Guo et al 2006, Kamenidou et al 2010, Bayat et al 2013, Whitted-Haag et al 2014, Dębicz et al 2016. A reaction of plants and varieties to silicon application might be related to different levels of endogenous gibberellins, what is suggested by Sivanesan et al [2013].…”
Section: Resultssupporting
confidence: 90%
“…A similar reaction of plants to silicon was observed in case of a 'Madelon' rose [De Kreij et al 1997]. Plants of Medicago sativa produced more stems per plant when the Si was applied [Guo et al 2006]. Silicon also increased a number of Calendula officinalis flowers by 35%, when plants were cultivated in a greenhouse under non-salt conditions, in comparison to the control [Bayat et al 2013].…”
Section: Resultsmentioning
confidence: 60%
“…Although plant height and number of leaves did not increase with Si fertilization, the reducing effects of drought on leaf and root size were partially or completely suppressed by Si fertilization. Other studies have also shown that Si improves root and leaf growth under drought stress condition (Adatia & Besford, 1986;Ahmed, Hassen, Qadeer, & Aslam, 2011;Guo, Lui, Tian, Zhang, & Wang, 2006;Hattori et al, 2005). Because root size, architecture and function enhance water and nutrient uptake, Si fertilization can increase drought tolerance in plants (Chaves et al, 2002;Ehdaie, Layne, & Waines, 2012;Hernandez-Apaolaza, 2014;Zhu & Gong, 2014).…”
Section: Discussionmentioning
confidence: 96%
“…Soil conditions play an important role in determining the extent to which eCO 2 and eT affect root nodulation in legumes ( Aranjuelo et al, 2014 ). Several studies report that supplementation of soil silicon (Si) levels promotes growth in legumes ( Horst and Marschner, 1978 ; Miyake and Takahashi, 1985 ; Guo et al, 2006 ; Johnson et al, 2017 ), though we know less about the functional role of Si in legumes compared to other plant families such as the Poaceae ( Epstein, 1999 ; Cooke and Leishman, 2011 ). Moreover, Si supplementation can increase rates of root nodulation and symbiosis with nitrogen fixing bacteria ( Nelwamondo and Dakora, 1999 ; Mali and Aery, 2008 ).…”
Section: Introductionmentioning
confidence: 99%